PENCABUTAN HAK PERWALIAN ANAK DAN PENUNJUKAN WALI DI PENGADILAN AGAMA KELAS 1A PADANG (Studi Putusan Pekara Nomor 455/Pdt.G/2021/PA.Pdg) - Fardi Marfin, MARDIUS dan (Fakultas Hukum Universitas Tamansiswa Padang, 2024)
Children are a trust and gift from the Almighty God, in whom the honor and dignity of being a complete human being is inherent. He also says that parents are obligated and responsible for their children. Guardianship is the authority given to a person to carry out legal acts as a representative for the interests and on behalf of a child who does not have both parents, or both parents or living parents are not capable of carrying out legal acts therefore, what is called a guardian is a person who is given the authority to take legal action in the interests of the child. The problem that the author raises in this thesis is how to implement the application for the revocation of child custody rights and the appointment of a study guardian in the decision in Case Number 455/Pdt.G/2021/PA.Pdg and what are the judge's considerations in revoking child custody rights and the appointment of a study guardian in the decision in Case Number 455 /Pdt.G/2021/PA. The author conducted research using a sociological juridical approach. Based on the results of the research, it can be concluded that: The implementation of the application for revoking the child's guardianship rights and the appointment of a guardian means that the biological grandmother applied for the revocation of the child's guardianship rights for the purpose of obtaining pension funds for the child's biological mother for survival, where the child is physically disabled and of course requires significant costs. pretty much. The judge's consideration in revoking the child's guardianship rights and appointing a guardian was that the petition for the lawsuit could be granted by determining that the child named Muhammad Zahran Fadhlur Rahman was under the guardianship of the plaintiff Roslian and the plaintiff as guardian had the right to take legal action because the child was abandoned (died) by his mother because the biological father neglected his obligations. and has handed over childcare to his biological grandmother.